STRATEGI PEMERINTAHAN DESA SEGARAN KECAMATAN DELANGGU KABUPATEN KLATEN DALAM PEMENUHAN HAK ANAK MENUJU DESA LAYAK ANAK - Octavia Monalisa Bela Dwi Paksi; Triyanto Triyanto; Rima Vien Permata Hartanto (Program Studi Pendidikan Pancasila dan Kewarganegaraan FKIP Universitas Sebelas Maret, 2018)
The aims of this research were: (1) to identify the strategies of Segaran Village Goverment to fulfill the children’s right in order to be children proper village, (2) the reveal the obstacles of Segaran Village Government to fulfill the children’s right in order to be children proper village, (3) to find out the solutions to handle the obstacles of fulfilling the children’s rights in order to be children proper village by Segaran Village Government. This research applied a descriptive qualitative research. The sources of the data were informants, events, and documents. The sample was chosen by purposive sampling technique. The data were obtained through interview, observation, and document analysis. The researcher triangulated the data obtained and the method used in order to have the valid data. On the other hand, the data were analyzed using interactive model, i.e.: (1) data collection, (2) data reduction, (3) data display, and (4) drawing conclusion. Meanwhile, the research was done through some procedures, namely: (1) pre-research, (2) data collection, (3) data analysis, and (4) research report writing.According to the results of the research, it can be summed up that: (1) the strategies of Segaran Village Goverment to fulfill the children’s right in order to be children proper village are by activating BKB cadres, cooperating with some village institutions, upgrading the village infrastructure, enhancing society awarness, applying sekolah sungai programs, applying jemput bola strategy, giving the birth certificate, and allocating the fund estimation of children proper village, (2) the obstacles of the government were the lack of the society awarness about the significance of children proper programs, the lack of the society participation, and the obstruction of the fund estimation, thus, the implementation of some programs were not done well. In addtition, some obstacles come from the dense of the society bussiness, the lack of communnication of the society and the government, and the inferiority of the society to respond the programs. The last conclusion deals with the soulution of the problems. The solution applied by the government was continous approaching to the society and arranging the priority according to its importance level. Additionally, the society keep increasing their participation to be actively involved and be open minded, critical, and smart to implement the programs of the governments. Keywords: strategies,Segaran Village government, children right, children proper village.